2019
DOI: 10.1111/jvp.12794
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and tissue residues of enrofloxacin in the largemouth bass (Micropterus salmoides) after oral administration

Abstract: The study was carried out to evaluate the pharmacokinetic disposition of enrofloxacin (ENF) with a single dose of 20 mg/kg after oral administration in largemouth bass (Micropterus salmoides) at 28°C. The concentrations of ENF and of its metabolite ciprofloxacin (CIP) in plasma, liver, and muscle plus skin in natural proportions were determined using HPLC. The concentration–time data for ENF in plasma were best described by a two‐compartment open model. After oral administration, the maximum ENF concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Shorter T 1/2λZ values have also been reported in rainbow trout, with the values ranging from 36.48 to 71.88 h in different tissues (19). However, longer muscle plus skin T 1/2λZ value (115.14 h) has been reported in largemouth bass (22). In the present study, it should be noted that only 2-4 samples, including plasma, kidney, liver, and skin-muscle, were quantified at the last quantifiable time point (360 or 480 h), and those samples with enrofloxacin concentrations below the LOQ were omitted and not used to calculate T 1/2λZ .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Shorter T 1/2λZ values have also been reported in rainbow trout, with the values ranging from 36.48 to 71.88 h in different tissues (19). However, longer muscle plus skin T 1/2λZ value (115.14 h) has been reported in largemouth bass (22). In the present study, it should be noted that only 2-4 samples, including plasma, kidney, liver, and skin-muscle, were quantified at the last quantifiable time point (360 or 480 h), and those samples with enrofloxacin concentrations below the LOQ were omitted and not used to calculate T 1/2λZ .…”
Section: Discussionmentioning
confidence: 92%
“…The plasma pharmacokinetics of enrofloxacin has been reported in some fish species, such as crucian carp (11,12), large yellow croaker (13), tilapia (14), snakehead fish (15), brown turbot (16), and salmonids (17). In addition to those pharmacokinetics studies, the tissue distribution of enrofloxacin has also been reported in aquaculture species, including northern snakeheads (18), rainbow trout (19,20), grass carp (21), largemouth bass (22), and pacu (23). Those previous results indicated that the plasma and tissues kinetics of enrofloxacin might be strongly influenced by fish species, body conditions, routes of administration, water temperature, and other environmental factors.…”
Section: Introductionmentioning
confidence: 96%
“…In our study, ciprofloxacin could not be detected in plasma samples taken after enrofloxacin administration. Although ciprofloxacin was detected at a low ratio in largemouth bass [ 10 ], crucian carp [ 38 ], grass carp [ 33 ] and rainbow trout [ 35 ], it was not detected in brown trout [ 4 ], rainbow trout [ 14 ] and sea bream [ 38 ]. It has been stated that the single dose administration of enrofloxacin in sea bass strongly inhibits the hepatic P450 enzymes system [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In both mammalian and nonmammalian species, enrofloxacin is dealkylated to ciprofloxacin, which exhibits a potency and spectrum of activity similar to enrofloxacin [ 7 ]. Enrofloxacin is widely used in fish due to its properties such as good absorption, large volume of distribution, high bioavailability, and long terminal half-life [ 9 , 10 ]. Although enrofloxacin is included in category B (Restrict) in the classification of antibiotics for veterinary use in terms of the risk of antimicrobial resistance by the EMA, it has been stated that it can be used in fish in cases in which there are few alternative treatment options, such as Aeromonas infection [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The determination of ENR and CIP were carried out based on our previously published HPLC methods ( 19 , 23 ). Shortly, 0.5 ml of plasma was extracted two times with 3 ml of acetonitrile.…”
Section: Methodsmentioning
confidence: 99%